Mental condition of human in the phraseological representation of the boundary (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article presents the results of the researching of phraseological units (FU) on the designation of the mental condition of man in the representation of the boundary. Different models of the human condition, which are objectified by FU, are revealed. The results of structural-semantic analysis of phraseologisms, which testify to universality and reveal specific features of the verbalization of the mental state of man are shown, the focus is on the peculiarities of the manifestation of the last units of the phraseological level. The shifting of attention to the paradigm of humanitarian knowledge towards anthropocentrism was marked by the formation of new research domains at the intersection of sciences studying people and the environment. In the phrase-semantic segment (FSS), the “limit of the mental state of man” has no absolute center, there is no phraseological unit that would call the mental state of a person in general, that is, would have a single component of meaning – an integral part. As part of the value of the FU there are at least two components – the component “ental condition in general” and component that specifies the nature of the condition. Mental state of man has basically two sources: firstly, it may be the result of past activity, and secondly, external factors or circumstances cause a certain emotional state, a feeling. Condition, in contrast to quality, is characterized by less firmness, the state is more likely to change, it depends not only on the internal signs of a person, but also on the external circumstances influencing it. FSS “the limit of the mental state of man” form FU, which have a common meaning, which expresses despair, impotence, hopelessness, joy, success: to strike a snag, willy-nilly, to be down in the dumps, to tread on air, etc. Phraseologisms verbalize the mental conditions of man by using the words of various sensations, their visualization (the identification of emotions, state, attitude is associated with the appearance of man, his eyes), various physiological reactions of the body, and physiological manifestations of mental states are associated with the phenomena of the external world, which become symbols of different psychic manifestations.It is indisputable that emotional factors are one of the sources of semantic language development, and emotional components are not beyond the lexical meaning of the word, but are its components.
Keywords: phraseological units; psychic condition of man; representation of boundaries; objectification; modeling; structural-semantic analysis